Self-authenticating genomic materials in Escherichia coli via advanced genome signatures - Zhaoguan Wang; Jingsong Cui; Qian Liu; Jiawei Li; Chi Guo; Yiyang Liu; Changyue Jiang; Hui Xue; Jiaojiao Li; Yonggang Ke; Hao Qi (Communications Biology)
Abstract The authenticity and integrity of synthetic genomic materials containing valuable intellectual property are essential for advancing scientific knowledge and enhancing biosafety. Nevertheless, existing DNA tags and watermarks have limited efficacy due to low mutation tolerance and inadequate digital encoding capacity. Here, we present “Genome Signature”, a biochemically stable and tamper-resistant DNA labeling system that enables the creation of self-authenticating genomes. Central to this system is a Golomb-ruler-derived Genome-Comb, which efficiently maps extensive nucleotide sequences onto limited codons within endogenous genes, significantly improving error correction and data encoding across millions of nucleotides. Using our labeling system, we successfully recorded a 4.5-million-nucleotide genome in living E. coli. The Genome Signature effectively encodes data within codon orders, and autonomously identifies and corrects mutations in our computing test, ensuring genome integrity and authenticity. Furthermore, it allows precise tracking of coded sequences across different cells, potentially advancing the development of reliable genomic materials in synthetic biology.